Peranan Kepolisian Dalam Upaya Penegakan Huku Terhadap Pelaku Tindak Pidana Pencabulan Anak (Studi Kasus di Kepolisian Resort Kota Padangsidimpuan) - Ray, Bryan; Wessy, Wessy; Marsella, Marsella (Universitas Medan Area, 2024)
The purpose of the research is to find out the role of the police in handling criminal acts of child abuse, to find out the obstacles in handling criminal acts of child abuse. The research method used is normative juridical research, namely research conducted aimed at examining the application of statutory provisions (positive law) relating to the crime of child abuse. The data collection technique is library research, and interviews with the Padangsidimpuan police, data analysis is by While the data analysis technique used is qualitative analysis, namely the data obtained is then arranged systematically and then analyzed qualitatively. From the results of the research that has been done, the author draws the conclusion that the role of the police in handling criminal acts of child abuse The role of the police in handling criminal acts of child abuse, Implementing coordination to the protection of women and children, Coordination to the social service, Coordination to the correctional center, Conducting counseling. obstacles in handling criminal acts of child abuse, the perpetrator escapes, the perpetrator is unknown, the victim does not want to talk.